1998
DOI: 10.1104/pp.117.2.667
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Stress on Cell Division and Cdc2-Like Cell Cycle Kinase Activity in Wheat Leaves1

Abstract: In wheat (Triticum aestivum) seedlings subjected to a mild water stress (water potential of ؊0.3 MPa), the leaf-elongation rate was reduced by one-half and the mitotic activity of mesophyll cells was reduced to 42% of well-watered controls within 1 d. There was also a reduction in the length of the zone of mesophyll cell division to within 4 mm from the base compared with 8 mm in control leaves. However, the period of division continued longer in the stressed than in the control leaves, and the final cell numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
125
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(131 citation statements)
references
References 67 publications
(74 reference statements)
3
125
0
3
Order By: Relevance
“…The shoot is affected by the drought stress. In response to drought stress, plants generally regulate the number and area of leaves to decrease the water demand (Schuppler et al, 1998).…”
Section: And Discussionmentioning
confidence: 99%
“…The shoot is affected by the drought stress. In response to drought stress, plants generally regulate the number and area of leaves to decrease the water demand (Schuppler et al, 1998).…”
Section: And Discussionmentioning
confidence: 99%
“…It is frequently observed that stress signals not only induce plant resistance but also affect growth rate and cell division. For example, in wheat (Triticum aestivum) seedlings subjected to a mild water stress, leaf elongation is reduced in correlation with a rapid decrease of mitotic activity in mesophyll cells of the first leaf (Schuppler et al, 1998). Similar effects were found in water-stressed roots of maize (Zea mays; Sacks et al, 1997) and sunflower (Helianthus annuus; Robertson et al, 1990), where an involvement of abscisic acid (ABA) in the inhibition of the cell cycle was suggested.…”
mentioning
confidence: 83%
“…This is accompanied by changes in the activity of the enzyme cdc2 kinase which plays a crucial role in the control of cell division (Schuppler et al, 1998). We have shown that maize leaf elongation rate is reduced by water deficit via two effects, one involving a hydraulic signal and the other linked to ABA signalling (Ben Haj Salah & Tardieu, 1997).…”
Section: Effects Of Water Availability and Of Intercepted Ppfdmentioning
confidence: 99%